RELATIONSHIPS TO READING LEARNING AND LEARNING MOTIVATION WITH STUDENTS WRITING STUDENTS OF SMU STATE KODYA PADANG - Gusnetti Gusnetti; Agustina Agustina; Ermanto Ermanto; Syahrul Syahrul; M Zaim (English Language Teaching and Research, 2018)
This article contains a discussion about the relationship of reading ability and motivation to learn with the ability to write high school students Kodya Padang. The purpose of writing this article to determine the relationship between the ability to read and motivation to the ability to write high school students of SMU  Kodya Padang. For this the authors use the theory of reading ability, learning motivation and ability. This type of research is quantitative because of its nature that contains a series of numbers so as to make predictions for the future. Type of research used test and questionnaire. The results showed based on the proposed hypothesis: (1) There is a significant relationship between the ability to read and write high school students  of SMUKodya Padang. (2) There is a significant correlation between learning motivation and writing skill of SMU Kodya Padang. (3) There is a significant correlation between reading ability and simultaneous learning motivation toward the writing skill of SMU Kodya Padang. Thus the research hypothesis Ho rejected and Ha accepted, of course the results showed that the students of SMU Kodya Padang utilize the ability to read and motivation to improve learning skills. They are not only limited to writing a free article, behind the theories they wrote.Key word: reading ability, motivation to learn, writing ability